PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS INSHOT MATERI SIKLUS AIR UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SDN GEDANGSEWU 1 - Dini Sri Utami; Mumun Nurmilawati; Poppy Rahmatika Primandiri (Jurnal Manajemen Pendidikan, 2026)
The purpose of this study is to determine the validity, practicality, and effectiveness of interactive multimedia based on inshot water cycle material for fourth grade elementary school students. The research to be conducted is Design Research type Development Research (DR). The development model used in this study is the development studies type with Formative Tessmer test. The subjects of this study were 26 fourth grade students of SDN Gedangsewu 1. The data analysis techniques used were qualitative descriptive analysis and quantitative descriptive analysis. Data collection instruments included observation sheets, interview sheets, expert validation sheets, and pretests and posttests. The results of this study indicate that. (1) The results of the validity score from media experts were 84% and material experts were 88%, both validation values ​​obtained very valid criteria. (2) The results of the teacher's practicality test were 90.5% and the average response score of 26 students Field test was 87.6%, both teacher and student practicality values ​​obtained very practical criteria. (3) The effectiveness test showed that 38.4% of students completed the pretest. Then, the posttest results showed that 88.5% of students completed the course. This increase indicates the effectiveness of learning using Inshot-Based Interactive Multimedia. It can be concluded that the development of Inshot-Based Interactive Multimedia is very valid, very practical, and effective for use in learning water cycle material in grade IV of SDN Gedangsewu 1. Inshot-Based Interactive Multimedia can increase student motivation and enthusiasm for learning in class.